Modelling of benzene distribution in the subsurface of an abandoned gas plant site after a long term of groundwater table fluctuation. Issue 22 (6th July 2012) - Yang, Qingshu; Li, Yan; Zhou, Jinfeng; Xie, Xiaoxi; Su, Yu; Gu, Qingbao; Kamon, Masashi
Abstract The non‐aqueous phase liquid simulator was used to model and interpret the occurrence of a thin benzene‐contaminated soil layer 9.0 m below the groundwater table in an abandoned gas plant site. The simulator was first evaluated in column tests under similar conditions to the contaminated site. Saturation–capillary pressure (S–P) relationships were extended from the laboratory scale of the column tests to the field scale of the subsurface at the abandoned site. Dynamic boundary conditions were established in order to prevent the model from generating excessive vertical velocities. The modelled benzene layer formation process agreed well with the in situ observations. With falling and then rising of the water table, benzene release from the surface migrated downward and then upward and distributed itself below and above the water table. Biochemical degradation of benzene made the distribution discontinuous in the subsurface. These two factors resulted in the thin benzene‐contaminated layer below the groundwater table. Copyright © 2012 John Wiley & Sons, Ltd.